1999
DOI: 10.1063/1.124577
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetoresistance in sintered granular manganite/insulator systems

Abstract: We report significant enhancements of magnetoresistance in granular (La0.67Ca0.33MnO3)x/(SrTiO3)1−x. The system exhibits a conduction threshold at x=xc∼60%, around which magnetoresistance versus x has a maximum. The composition xc at which maximum enhancement in magnetoresistance is observed is the same at high (around 5 T) and at low (a few hundred Oersted) fields. The enhancement is consistent with the disorder-driven amplification of spin-dependent transport at the structural boundaries of the mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
119
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(141 citation statements)
references
References 20 publications
7
119
4
Order By: Relevance
“…It is found that the conductivity, G, decrease as Gϰe x , as typically found in other percolating systems. 18 The RT magnetoresistance of the sample with xϭ1 and in the H ʈ geometry is shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the conductivity, G, decrease as Gϰe x , as typically found in other percolating systems. 18 The RT magnetoresistance of the sample with xϭ1 and in the H ʈ geometry is shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…One of the routes used is the reduction of the conduction path by diluting LSMO powders with a magnetic insulator ͑MI͒ 9,10 or a nonmagnetic insulator ͑NMI͒. 11,12 In fact, LFMR responses obtained in diluted LSMO/NMI composites have demonstrated to be adequate for some technological applications, such as potentiometers, position sensors, etc. 2 From the technological point of view to develop competitive low cost magnetic sensors, based on the LFMR response of manganite materials, involves two different aspects:…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have also been made to increase the MR through the formation of some composites. [9][10][11] Recently our work on La 0.67 Ca 0.33 MnO 3 ͑LCMO͒:SiO 2 composite 11 showed interesting results. The composite showed a percolation threshold composition corresponding to 90 vol % of LCMO, beyond which the resistivity shoots up sharply to almost 6 orders of magnitude.…”
mentioning
confidence: 99%
“…The presence of non-magnetic insulating phase should also result in a variation of the electrical transport behavior, since the samples now consist of manganite/insulator mixture. Petrov et al [5] found the room temperature resistivity of LCMO/SrTiO 3 manganite/insulator mixture increases by about four orders of magnitude to ∼10 2 m when the LCMO fraction decreases to <0.3. The room temperature resistivity in the present work is found to be in the range 10 1 -10 2 m, clearly supporting the magnetization results of manganite phase dilution and also in agreement with the results of Petrov et al…”
Section: Resultsmentioning
confidence: 99%
“…They find that the resistivity increases with increasing Cr and exhibits a double peak behavior for Cr ≤ 0.2. The MR, however, reaches a value of only 40% in fields as high as 6.0 T. Petrov et al [5] find that the MR is greatly enhanced when La 0.67 Ca 0.33 MnO 3 (LCMO) is mixed with a non-magnetic insulator, such as SrTiO 3 . The MR exhibits a peak at a conduction threshold of 60% LCMO.…”
Section: Introductionmentioning
confidence: 99%